Epidemiology, Pathogenesis, and Control of a Tick-Borne Disease- Kyasanur Forest Disease: Current Status and Future Directions - Shah, Syed Z.; Jabbar, Basit; Ahmed, Nadeem; Rehman, Anum; Nasir, Hira; Nadeem, Sarooj; Jabbar, Iqra; Rahman, Zia ur; Azam, Shafiq (Frontiers in Cellular and Infection Microbiology, 2018)
In South Asia, Haemaphysalis spinigera tick transmits Kyasanur Forest Disease Virus (KFDV), a flavivirus that causes severe hemorrhagic fever with neurological manifestations such as mental disturbances, severe headache, tremors, and vision deficits in infected human beings with a fatality rate of 3–10%. The disease was first reported in March 1957 from Kyasanur forest of Karnataka (India) from sick and dying monkeys. Since then, between 400 and 500 humans cases per year have been recorded; monkeys and small mammals are common hosts of this virus. KFDV can cause epizootics with high fatality in primates and is a level-4 virus according to the international biosafety rules. The density of tick vectors in a given year correlates with the incidence of human disease. The virus is a positive strand RNA virus and its genome was discovered to code for one polyprotein that is cleaved post-translationally into 3 structural proteins (Capsid protein, Envelope Glycoprotein M and Envelope Glycoprotein E) and 7 non-structural proteins (NS1, NS2A, NS2B, NS3, NS4A, NS4B, and NS5). KFDV has a high degree of sequence homology with most members of the TBEV serocomplex. Alkhurma virus is a KFDV variant sharing a sequence similarity of 97%. KFDV is classified as a NIAID Category C priority pathogen due to its extreme pathogenicity and lack of US FDA approved vaccines and therapeutics; also, the infectious dose is currently unknown for KFD. In India, formalin-inactivated KFDV vaccine produced in chick embryo fibroblast is being used. Nevertheless, further efforts are required to enhance its long-term efficacy. KFDV remains an understudied virus and there remains a lack of insight into its pathogenesis; moreover, specific treatment to the disease is not available to date. Environmental and climatic factors involved in disseminating Kyasanur Forest Disease are required to be fully explored. There should be a mapping of endemic areas and cross-border veterinary surveillance needs to be developed in high-risk regions. The involvement of both animal and health sector is pivotal for circumscribing the spread of this disease to new areas.